Use of electrical resistance to detect the formation and decomposition of methane hydrate - Zhou, Xitang; Fan, Shuanshi; Liang, Deqing; Wang, Donglei; Huang, Ningsheng (2007)
The changes of electrical resistance (R) were studied experimentally in the process of CH4 hydrate formation and decomposition, using temperature and pressure as the auxiliary detecting methods simultaneously. The experiment results show that R increases with hydrate formation and decreases with hydrate decompositon. R is more sensitive to hydrate formation and decompositon than temperature or pressure, which indicates that the detection of R will be an effective means for detecting natural gas hydrate (NGH) quantitatively.